THE STUDENTS PHONOLOGICAL AWARENESS ON READING COMPREHENSION AT SENIOR HIGH SCHOOL - Alamsyah, Nursyahreni; Haq, Muhammad Zia Ul (English Language Teaching Methodology, 2023)
This research aims to find out the significant correlation between students` phonological awareness and reading comprehension at senior high school. This research employs a descriptive quantitative research design. The research population consisted of 21 samples from Ma Pesantren Al-Tenth Qamar's grade. Purposive sampling was used, and data was collected using phonological awareness and reading comprehension tests. The data was analyzed using SPSS 25.0 by the researcher. The average of the phonological awareness test was 79,28, and the average of the reading comprehension test was 72,85, based on findings of this study. At the 0.05 level of significance, the correlation coefficient was 0.711. The correlation coefficient (0.711) was within the range of 0.600 - 0.800, indicating that the interpretation of correlation could be classified as enough. Based on the findings, it was possible to conclude that the correlation coefficient Ha was accepted. As a result, there was a strong relationship between students' phonological awareness and reading comprehension